2015
DOI: 10.1002/ejoc.201500582
|View full text |Cite
|
Sign up to set email alerts
|

Fused Selenazolinium Salt Derivatives with a Se–N+ Bond: Preparation and Properties

Abstract: Stimuli‐responsive metal–organic polyhedra (srMOPs) functionalized with azobenzene showed UV‐irradiation‐induced isomerization from the insoluble trans‐srMOP to the soluble cis‐srMOP, whereas irradiation with blue light reversed this process. Guest molecules were trapped and released upon cis‐to‐trans and trans‐to‐cis isomerization of the srMOPs, respectively. This study provides a new direction in the ever‐diversifying field of MOPs, while laying the groundwork for a new class of optically responsive material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Firstly, solvates are described followed by co-crystals. The chemical structures of the 20 compounds covered in this section, 204 – 224 [118] , [233] , [234] , [235] , [236] , [237] , [238] , [239] , [240] , [241] , [242] , [243] , [244] , [245] are shown in Fig. 25 .…”
Section: Supramolecular Assemblies Of Multi-component Species Mediatementioning
confidence: 99%
“…Firstly, solvates are described followed by co-crystals. The chemical structures of the 20 compounds covered in this section, 204 – 224 [118] , [233] , [234] , [235] , [236] , [237] , [238] , [239] , [240] , [241] , [242] , [243] , [244] , [245] are shown in Fig. 25 .…”
Section: Supramolecular Assemblies Of Multi-component Species Mediatementioning
confidence: 99%
“…Synthesis of 3-bromo-selenazolopyridinium chlorides 1 – 7 and 3-bromo-2-(1-hydroxycyclohexyl)[1,2]selenazolo[2,3- b ]thiazolinium chloride 8 ( Figure 1 ) was described elsewhere [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The selenazolinium salts: 3-bromo-2-(1-hydroxy-1-methylethyl)[1,2]selenazolo[2,3- a ]pyridinium chloride ( 1 ), 3-bromo-2-(1-hydroxy-1-phenylethyl)[1,2]selenazolo[2,3- a ]pyridinium chloride ( 2 ), 3-bromo-2-(1-hydroxycyclohexyl)[1,2]selenazolo[2,3- a ]pyridinium chloride ( 3 ), 3-bromo-2-(1-hydroxycyclohexyl)-5-methyl[1,2]selenazolo[2,3- a ]pyridinium chloride ( 4 ), 3-bromo-7-formyl-2-(1-hydroxycyclohexyl)[1,2]selenazolo[2,3- a ]pyridinium chloride ( 5 ), 3-bromo-2-(1-hydroxycyclohexyl)-7-(2-hydroxypropan-2-yl)[1,2]selenazolo[2,3- a ]pyridinium chloride ( 6 ), 3-bromo-2-(1-hydroxycycloheptyl)[1,2]selenazolo[2,3- a ]pyridinium chloride ( 7 ), and 3-bromo-2-(1-hydroxycyclohexyl)[1,2]selenazolo[2,3- b ]thiazolinium chloride ( 8 ) were synthesized according to the procedures described previously [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactivity of selenium in compounds, for instance in the isoselenazole ebselen, can also be improved considerably by placing a positive charge at the nitrogen in the selenium-nitrogen bond. As Arsenyans and his colleagues have shown, the resulting selenazolinium salts are incredibly reactive and also active against a wide range of cancer cell lines [ 98 ]. Similarly, Handzlik and her colleagues, employing the same palette of selenazolinium salts have demonstrated that such compounds also act against certain resistant strains of bacteria [ 59 ].…”
Section: Redox Catalysts With Sensor/effector Propertiesmentioning
confidence: 99%